HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAQ DI KELAS VIII PP MTs AS – SALAM DESA GERINGGING BARU KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Shanty Hapsari; Andrizal Andrizal; Alhairi Alhairi (Universitas Islam Kuantan Singingi, 2020)
This research was conducted aiming to find out whether there is a relationship between intellectual intelligence and emotional intelligence. This type of research is quantitative correlation with data collection techniques observation, interview, instrument distribution, and documentation. And analysis techniques using the validity test, realibility test, and simple linear correlation hypothesis.The results of this study are that are still many students who have emotional intelligence as much 56,5%, high 29%, and low 14,5%. And the academic achievement of students moral values is very good 8,7%, good 24,6%, and enough 66,7%. And there is positive relationship between IQ and EQ on the academic achievement of akidah akhlaq students proven by the correlation test using SPSS and the result are 0,694%. Frm the result is concluded that if students are able to balance IQ and EQ will be able to improve learning achievement specifically on akidah akhlaq.